Crosstalk between AhR and wnt/β-catenin signal pathways in the cardiac developmental toxicity of PM2.5 in zebrafish embryos. (29th April 2016) - Zhang, Hang; Yao, Yugang; Chen, Yang; Yue, Cong; Chen, Jiahong; Tong, Jian; Jiang, Yan; Chen, Tao
Abstract: Recent studies have shown an association between congenital heart defects and air fine particle matter (PM2.5), but the molecular mechanisms remain elusive. It is well known that a number of organic compounds in PM2.5 can act as AhR agonists, and activation of AhR can antagonize Wnt/β-catenin signaling. Therefore, we hypothesized that PM2.5 could activate AhR and then repress the expression of wnt/β-catenin targeted genes essential for cardiogenesis, resulting in heart defects. To test this hypothesis, we investigated the effects of extractable organic matter (EOM) from PM2.5 on AhR and Wnt/β-catenin signal pathways in zebrafish embryos. We confirmed that EOM could cause malformations in the heart and decreased heart rate in zebrafish embryos at 72hpf, and found that the EOM-induced heart defects were rescued in embryos co-exposed with EOM plus AhR antagonist CH223191 or β-catenin agonist CHIR99021. We further found that EOM had increased the expression levels of AhR targeted genes (Cyp1a1, Cyp1b1 and Ahrra) and reduced the mRNA levels of β-catenin targeted genes (axin2, nkx2.5 and sox9b). The mRNA expression level of Rspo2, a β-catenin upstream gene, was also decreased in embryos exposed to EOM. Supplementation with CH223191 or CHIR99021 attenuated most of the EOM-induced expression changes of genes involved in both AhR and wnt/β-catenin signal pathways. However, the mRNA expression level of AhR inhibitor Ahrrb, which did not change by EOM treatment alone, was increased in embryos co-exposed to EOM plus CH223191 or CHIR99021. We conclude that the activation of AhR by EOM from PM2.5 might repress wnt/β-catenin signaling, leading to heart defects in zebrafish embryos. Furthermore, our results indicate that the cardiac developmental toxicity of PM2.5 might be prevented by targeting AhR or wnt/β-catenin signaling.